Immune-related thyroid dysfunction as a positive prognostic factor for patients with lung cancer in China: a real-world retrospective study - Guo, Ge; Jing, Zihan; Dou, Wenrui; Wang, Guiqin; Dang, JunJie; Li, Yajie; Wang, Ruqiong; Zhang, Huan; Sun, Jing; Shang, Lihua (Frontiers in Immunology, 2024)
IntroductionThe relationship between immune-related thyroid dysfunction (irTD) and survival rates in cancer patients remains unclear. Furthermore, the impact of variations in immunotherapy line numbers and pathological types among lung cancer patients on this relationship has not been fully elucidated. This study aims to evaluate the potential of irTD as a prognostic marker for immunotherapy in Chinese patients with lung cancer.MethodsA retrospective analysis was conducted on data collected from patients with locally advanced or metastatic lung cancer who received immune checkpoint inhibitor treatment at the Harbin Medical University Cancer Hospital. The study period spanned from December 1, 2016, to November 30, 2023. The primary endpoints were progression-free survival (PFS) and overall survival (OS), while the objective response rate served as the secondary endpoint.ResultsAmong the 361 patients in this study, 42.7% developed irTD. Significant differences were observed between the groups with and without irTD regarding inflammatory indices, thyroid-stimulating hormone levels, and thyroid autoantibody positivity (P < 0.05). Patients with irTD demonstrated longer OS (32.5 vs. 22 months, HR: 0.65, 95% CI: 0.49-0.88; P = 0.005). For NSCLC patients, OS was significantly prolonged in those with irTD (40.8 vs. 27.2 months, HR: 0.68, 95% CI: 0.48-0.96; P = 0.028). Similarly, SCLC patients who developed irTD exhibited longer OS (27.9 vs. 13.8 months, HR: 0.51, 95% CI: 0.29-0.90; P = 0.022). Notably, irTD was observed exclusively in patients receiving immunotherapy in the second or later lines, showing a significant association with extended OS (40.8 vs. 19.4 months, HR: 0.56, 95% CI: 0.35-0.88; P = 0.012), while the presence of irTD during first-line immunotherapy did not confer a benefit to patients (32.4 vs 24.5 months, HR: 0.74, 95% CI: 0.50-1.10; P = 0.134). The effects of different irTD types, severities, or clinical symptoms on PFS and OS did not differ significantly (P > 0.05).ConclusionirTD demonstrates potential as a predictive marker for long-term survival benefits in Chinese patients with lung cancer. However, our exploratory analysis indicates that this association was exclusively observed in individuals receiving immunotherapy as a second-line or subsequent treatment.